Postcards from the Baja California border : portraying townscape and place, 1900s-1950s - Arreola, Daniel D. (Daniel David), 1950- (University of Arizona Press, 2021)
"Postcards have a magical pull. They allow us to see the past through charming relics that allow us to travel back in time. Daniel D. Arreola's Postcards from the Baja California Border offers a window into the historical and geographical past of storied Mexican border communities. Once-popular tourist destinations from the 1900s through the 1950s, the border communities explored in Postcards from the Baja California Border used to be filled with revelers, cabarets, curio shops, and more. The postcards in this book show the bright and dynamic past of California's borderlands while diving deep into the historic and geographic significance of the imagery found on the postcards. This form of place study calls attention to how we can see a past through a serial view of places, by the nature of repetition, and the photographing of the same place over and over again. Arreola draws our focus to townscapes, or built landscapes, of four border towns--Tijuana, Mexicali, Tecate, and Algodones--during the first half of the twentieth century. With an emphasis on the tourist's view of these places, this book creates a vivid picture of what life was like for tourists and residents of these towns in the early and mid-twentieth century."